2018
DOI: 10.1163/15685373-12340025
|View full text |Cite
|
Sign up to set email alerts
|

Costs do not Explain Trust among Secular Groups

Abstract: Many human groups achieve high levels of trust and cooperation, but these achievements are vulnerable to exploitation. Several theorists have suggested that when groups impose costs on their members, these costs can function to limit freeriding, and hence promote trust and cooperation. While a substantial body of experimental research has demonstrated a positive relationship between costs and cooperation in religious groups, to date, this relationship has not held for secular groups. Here we extend this line o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…The results showed that while the number of costly requirements positively predicted the longevity of religious communes, the same requirements did not predict the survival of secular communes. A similar result was obtained in an experimental study where we tested the effects of costly requirements posed by various student groups on a US university campus (Shaver, DiVietro, et al, 2018). Specifically, we compared the frequency of costly requirements between fraternities, university clubs, and classes, and tested their effects on a trust-based cooperation.…”
Section: The Adaptive Benefits Of Collective Ritualssupporting
confidence: 78%
See 1 more Smart Citation
“…The results showed that while the number of costly requirements positively predicted the longevity of religious communes, the same requirements did not predict the survival of secular communes. A similar result was obtained in an experimental study where we tested the effects of costly requirements posed by various student groups on a US university campus (Shaver, DiVietro, et al, 2018). Specifically, we compared the frequency of costly requirements between fraternities, university clubs, and classes, and tested their effects on a trust-based cooperation.…”
Section: The Adaptive Benefits Of Collective Ritualssupporting
confidence: 78%
“…The studies by Sosis and Bressler (2003) and by Shaver, DiVietro, et al (2018) indicate that while collective rituals (especially in their costly form) contribute to the stabilization of risky collective action, the interaction between collective rituals and belief is even more effective. As I proposed above, collective rituals evolved from rudimentary dyadic signals to reliable signals of commitment to group-specific norms.…”
Section: The Adaptive Benefits Of Collective Ritualsmentioning
confidence: 99%
“…At the same time, sociality leaves individuals vulnerable to exploitation by conspecifics [10]. Under such conditions, collective resources are more likely to emerge and stabilize when individuals can reliably communicate their commitment to group goals that motivate collective action and resource production [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, collective rituals are also a public venue for communicating commitment to supernatural agents and the norms they impose on believers [ 80 82 ]. However, the commitment is not signaled only to other believers but also to oneself as a form of auto-signaling reassuring participants about their beliefs in supernatural agents [ 58 , 83 , 84 ]. Hearing religious music may be a subconscious reminder of participation in rituals, strengthening the auto-communicated commitment signals.…”
Section: Discussionmentioning
confidence: 99%